Prevalence and Risk Factors of Urinary Dysfunction in Post-Cesarean Patients: Urinary Dysfunction in Post-Cesarean Patients - Ahmad, Basharat; Safdar, Sabah; Heema, .; Hassan, Hira; Inayat, Zoopash; Karim, Sadia Binte (Pakistan Journal of Health Sciences, 2025)
Urinary dysfunction (UD) following cesarean section (CS) is a significant but underexplored maternal health issue. While vaginal delivery is traditionally associated with pelvic floor disorders, emerging evidence suggests cesarean delivery may also pose risks. Objectives: To determine the prevalence of UD and its associated risk factors among post-CS women in Peshawar, Pakistan. Methods: This cross-sectional study was conducted at Peshawar Institute of Medical Sciences, Peshawar, including 195 postpartum women who underwent CS between January to March 2024. Participants were contacted via telephone and assessed using a standardized proforma, including the International Prostate Symptom Score (IPSS) to evaluate urinary symptoms. Statistical analysis was performed using SPSS version 25.0. To identify the potential risk factors, logistic regression was performed. Results: The prevalence of UD was 31 (15.8%). Common symptoms included urgency (74.2%), incomplete bladder emptying (54.8%), and urinary frequency (41.9%). Stress urinary incontinence was observed in 38.7%. Significant risk factors included age >35 years (p<0.0001), emergency CS (p=0.0001), operating time >60 minutes (p<0.0001), baby weight >4 kg (p=0.0001), and BMI >30 kg/m² (p<0.0001). Emergency CS was the strongest predictor (OR=6.31, p<0.001). Conclusions: Urinary dysfunction is a notable concern following cesarean delivery. Emergency CS, obesity, and prolonged surgery are key risk factors. Early identification and preventive strategies may improve postpartum care outcomes.